An Investigation into the Impact of Constructivistic Approach on Islamic Education through the Digital Mind Mapping Frame - Hossein Salarian; Sara Jafari Namin (Permata : Jurnal Pendidikan Agama Islam, 2025)
This research aims to analyze the integration of constructivist approaches with MindMeister technology in improving students' understanding of Islamic Education learning in the context of Fiqh Muamalah in the digital era. The research uses a qualitative method with a library research approach through a comprehensive analysis of relevant scientific literature. To this end, three main problem formulations of the urgency of a constructivist approach in learning Fiqh Muamalah in the digital era, strategies and steps for the implementation of digital mind mapping based on MindMeister, as well as the integration of these two approaches for improving students’ understanding were examined. The results of the study showed that the urgency of the constructivist approach in the learning of Fiqh Muamalah lies in the need to transform the learning paradigm towards student-centered learning that is responsive to the characteristics of digital natives, with the complexity of the concept of Fiqh Muamalah which requires the construction of active knowledge through social interaction and metacognitive reflection. MindMeister's implementation strategy followed a systematic framework with four main strategies: technology adaptation, constructivist pedagogy, learning differentiation, and continuous assessment, which are implemented through three stages, namely preparation and needs analysis, mind map template design, and implementation with continuous monitoring. Constructivist-MindMeister integration has been shown to improve students’ understanding through three fundamental mechanisms: collaborative knowledge construction, adaptive digital scaffolding, and structured metacognitive reflection, which results in improvements in the dimensions of conceptual, procedural, and contextual understanding. This research contributes to the development of the Islamic Digital Pedagogy Framework and provides innovative recommendations for professional development, adaptive assessment, research partnerships, and blended learning models in contemporary Islamic education. Keywords: Constructivistic approach; Mindmeister; Digital Mind Mapping; Islamic Education; Fiqh Muamalah